2002
DOI: 10.1093/humrep/17.3.704
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryopreservation on sperm morphology, motility and mitochondrial function

Abstract: Sperm morphology, motility, mitochondrial activities and viability are equally susceptible to cryopreservation-induced damage. R123 intensity is a novel and robust indicator of mitochondrial function before and after such trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
216
0
25

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(257 citation statements)
references
References 27 publications
16
216
0
25
Order By: Relevance
“…14 Yet another study showed that the progressively motile sperms were found to decrease by 41% and the motile sperms by 33% after freezing and thawing. 11 However, we could not find any study in the past that was found to study the effect of motility in the prolonged post thaw interval. So we went a step ahead, waited for 40 min, while incubating the post wash swim up at 37 C and then analysed it.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…14 Yet another study showed that the progressively motile sperms were found to decrease by 41% and the motile sperms by 33% after freezing and thawing. 11 However, we could not find any study in the past that was found to study the effect of motility in the prolonged post thaw interval. So we went a step ahead, waited for 40 min, while incubating the post wash swim up at 37 C and then analysed it.…”
Section: Discussionmentioning
confidence: 91%
“…10 Therefore; an impairment of mitochondrial activity may explain the reduction in motility. 11 Although motility is not directly related to the fertilizing capacity, it is one of the most important factors affecting the sperm quality. 12 According to Keel and Webster, 1993, it has been documented that the motility of sperms is found to decrease by 50% after the freeze thaw cycle.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of freezing and thawing, physical and chemical stress to the sperm membrane are produced, leading to loss of sperm viability and fertilizing ability [2]. ROS are produced by a wide variety of exogenous chemicals and metabolic processes causing a broad spectrum of damage to the biological system.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation of human semen represents a useful therapeutic option in the management of infertility with several indications [1]. However, during cryopreservation, spermatozoa are exposed to physical and chemical stress that results in adverse changes in membrane lipid composition, sperm motility, viability and acrosome status [2][3][4][5][6]. All these changes reduce the fertilizing ability of human spermatozoa after cryopreservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Motility depends on endogenous ATP to transport chemical energy, and reduced motility may be associated with mitochondrial damage (O'Connell et al, 2002). Carp (Cyprinus carpio) sperm motility quits when 50 to 80% of ATP is exhausted via hydrolysis (Billard et al, 1995).…”
Section: Sperm Quality Parametersmentioning
confidence: 99%